Validity and reliability of the Polish adaptation of the work-related sense of coherence scale - Arkadiusz M. Jasiński; Romuald Derbis; Magdalena Wrzesińska; Martin Tušl; Georg F. Bauer (BMC Psychology)
Abstract Background Work-related sense of coherence (Work-SoC) is defined as the perceived comprehensibility, manageability and meaningfulness of an individual’s work situation. The purpose of this study was to investigate the factor structure, invariance, reliability, and validity of the Polish version of the Work-SoC Scale. Method The research was carried out between September and November 2023 in a diverse sample of employees. Factor structure, internal consistency, and measurement equivalence analysis were performed on sample N1 = 622. Criterion validity was checked on sample N2 = 255. Temporal stability was checked on sample N3 = 60 using the test-retest method. Results A three-factor solution was the best fit for the data, and invariant across sex, age, occupational group, and education. The Work-SoC was strongest in white-collar workers. Strength of Work-SoC was positively related to seniority (r = 0.23, p < 0.001). The reliability of the Work-SoC Scale was high (α = 0.84, ω = 0.84). Work-SoC was positively correlated with general SoC (r = 0.36, p < 0.001) and job satisfaction (r = 0.50, p < 0.001), and negatively correlated with job burnout (r = -0.32, p < 0.001). The temporal stability of the measurement for the overall scale was high (r = 0.80, p < 0.001). Conclusion The Polish adaptation of the Work-SoC Scale has an identical structure and is as reliable as the original version. The high criterion validity, measurement stability, and the invariant structure of the scale by sex, age, occupational group, and education suggest that the Work-SoC Scale is a valuable tool for future research on employee health.